E. COLI LPS AND LUGOL’S IODINE ON CONCEPTION RATE IN REPEAT BREEDER COWS WITH SUBCLINICAL ENDOMETRITIS - RAJU, F SEBASTIN; KANTHARAJ, S; MURUGAVEL, K; PERUMAL, S VENKATESA; ANTOINE, D (The Indian Journal of Animal Reproduction, 2021)
Forty-five repeat breeder cows positive for subclinical endometritis were divided randomly into three groups. Group-I (LPS) cows were administered 100 μg of E. coli LPS in 30 ml sterile phosphate buffered saline (PBS) intrauterine once at estrus. Group-II (LI) cows were administered 1% Lugol’s iodine in 30 ml of distilled water. Group- III (Control) cows were administered 30 ml sterile PBS intrauterine once at estrus. AI was done in the subsequent estrus in all the cows. Haematological parameters such as Hb, TLC and DLC were studied before initiation of treatment and on the subsequent estrus. Pregnancy verification was done on 45th day post AI. The mean Hb level significantly increased in LPS and LI groups in subsequent estrus. The TLC count significantly decreased in LPS and LI groups in subsequent estrus. There was significant increase in the mean lymphocyte count and significant decrease in neutrophil count in LPS group in subsequent estrus. There was significant decrease in monocyte count in LPS, control group and significant decrease in the eosinophil count in LI group in the subsequent estrus. The first service conception rate was 53.33%, 20.00 % and zero percent for LPS, LI and control groups, respectively.